Rotaxane rings promote oblique packing and extended lifetimes in DNA-templated molecular dye aggregates - Matthew S. Barclay (Nature Portfolio, 2021)
DNA templating is a useful strategy to control the positioning and aggregation of molecular dyes on a sub-nanometer scale, but sub-angstrom control is desirable for the precise tailoring of excitonic properties. Here, the authors show that templating squaraine dyes functionalized with rotaxane rings promotes an elusive oblique packing arrangement and extended excited-state lifetimes.